Model Online Problem Based Learning (e-PBL) Terintegrasi Etnoekologi untuk Meningkatkan Literasi Lingkungan Mahasiswa Pendidikan Biologi - Yeyendra Yeyendra; Mellisa Mellisa; Ibnu Hajar; Sandra Puspitasari; Rosi Santika (STAI Auliaurrasyidin Tembilahan, 2024)
The implementation of the problem based learning (PBL) model in online learning or what is abbreviated as e-PBL is an alternative model that can be used during learning to improve and maintain the quality of online learning. This research aims to determine the effect of implementing the ethnoecological integrated Online Problem Based Learning (e-PBL) learning model to increase the environmental literacy of biology education students. The method used is Quasi-Experimental Design using Non-equivalent. The research subjects were students of the Biology Education Study Program, FKIP, Riau Islamic University. Data analysis was carried out using the MSELS (Middle School Environmental Literacy Survey) questionnaire which was adapted based on the scientific integration applied. The research results show that the independent sample t test value has a Sig value. (2-tailed) <0.05 between experimental and control classes. In conclusion, the ethnoecological integrated e-PBL learning model influences the environmental literacy abilities of biology education students.